Prawa osób pozbawionych wolności w świetle Konstytucji RP i Kodeksu karnego wykonawczego - Myrna, Bogdan (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is an analysis of the rights of people sentenced to imprisonment specified in the Constitution and the Implementing Criminal Code. Referring to the two legal instruments, the author examines the rights of prisoners, people sentenced to militarycustody, people convicted of and sentenced for petty offences, people under arrest as well as detainees.
Keywords: prawa; obowiązki; status prawny skazanych; kara pozbawienia wolności